Effect of Intravaginal Prasterone on Sexual Dysfunction in Postmenopausal Women with Vulvovaginal Atrophy. (23rd November 2015) - Labrie, Fernand; Derogatis, Leonard; Archer, David F.; Koltun, William; Vachon, Andrée; Young, Douglas; Frenette, Louise; Portman, David; Montesino, Marlene; Côté, Isabelle; Parent, Julie; Lavoie, Lyne; et al.
Abstract: Introduction: Previous data have shown that intravaginal dehydroepiandrosterone (DHEA, prasterone) improved all the domains of sexual function, an effect most likely related to the local formation of androgens from DHEA. Aims: To confirm in a placebo‐controlled, prospective, double‐blind and randomized study the benefits of daily intravaginal DHEA for 12 weeks on sexual function using the Female Sexual Function Index (FSFI) questionnaire. Methods: Placebo was administered daily to 157 women while 325 women received 0.50% (6.5 mg) DHEA daily for 12 weeks. All women were postmenopausal meeting the criteria of vulvovaginal atrophy (VVA), namely moderate to severe dyspareunia as their most bothersome symptom of VVA in addition to having ≤5% of vaginal superficial cells and vaginal pH > 5.0. The FSFI questionnaire was filled at baseline (screening and day 1), 6 weeks and 12 weeks. Comparison between DHEA and placebo of the changes from baseline to 12 weeks was made using the analysis of covariance test, with treatment group as the main factor and baseline value as the covariate. Main Outcome Measures: The six domains and total score of the FSFI questionnaire were evaluated. Results: The FSFI domain desire increased over placebo by 0.24 unit (+49.0%, P  = 0.0105), arousal by 0.42 unit (+56.8%, P  = 0.0022), lubrication by 0.57 unit (+36.1%, P  = 0.0005), orgasm by 0.32 unit (+33.0%, P  = 0.047), satisfaction by 0.44 unit (+48.3%, P  = 0.0012), and pain at sexual activity by 0.62 unit (+39.2%, P  = 0.001). The total FSFI score, on the other hand, has shown a superiority of 2.59 units in the DHEA group over placebo or a 41.3% greater change than placebo ( P  = 0.0006 over placebo). Conclusion: The present data show that all the six domains of the FSFI are improved over placebo (from P  = 0.047 to 0.0005), thus confirming the previously observed benefits of intravaginal DHEA on female sexual dysfunction by an action exerted exclusively at the level of the vagina, in the absence of biologically significant changes of serum steroids levels.Fernand Labrie, Leonard Derogatis, David F. Archer, William Koltun, Andrée Vachon, Douglas Young, Louise Frenette, David Portman, Marlene Montesino, Isabelle Côté, Julie Parent, Lyne Lavoie, Adam Beauregard, Céline Martel, Mario Vaillancourt, John Balser, Érick Moyneur, and Members of the VVA Prasterone Research Group. Effect of Intravaginal Prasterone on Sexual Dysfunction in Postmenopausal Women with Vulvovaginal Atrophy. J Sex Med 2015;12:2401–2412.